A prognostic model incorporating the albumin-corrected anion gap in patients with aneurysmal subarachnoid hemorrhage - Wang, Ruoran; Rong, Juan; Xu, Jianguo; He, Min (Frontiers in Neurology, 2024)
Background: Aneurysmal subarachnoid hemorrhage (aSAH) patients have poor prognoses. The anion gap (AG) has been verified related with the mortality of various critically ill patients. While the true level of AG would be underestimated with the hypoalbuminemia. This study was performed to verify the prognostic value of single AG and albumin-corrected anion gap (ACAG) among aSAH patients.Methods: Significant factors in the univariate logistic regression were included into the multivariate logistic regression to explore risk factors of mortality of aSAH patients and confirm the independent relationship between ACAG and mortality.The restricted cubic spline (RCS) was used to visually show the relationship between ACAG level and mortality risk of aSAH patients. The predictive model for mortality was developed by incorporating significant factors in the multivariate logistic regression. The prognostic value of ACAG and the developed model was evaluated by calculating the AUC (area under the receiver operating characteristics curve).Results: 144 aSAH patients suffered 30-day death with a mortality rate of 20.3%. The positive relationship between ACAG level and the mortality of aSAH was shown by the RCS curve. The multivariate logistic regression discovered that only six factors were finally and independently related with the mortality of aSAH after adjusting confounding effects including Hunt Hess (p=0.006), surgical options (p<0.001), white blood cell (p<0.001), serum chloride (p=0.023), ACAG (p=0.039), delayed cerebral ischemia (p<0.001). The AUC of AG, albumin, and ACAG for predicting mortality of aSAH was 0.606, 0.536, and 0.617, respectively. Composed of Hunt Hess, surgical options, white blood cell, serum chloride, ACAG, and delayed cerebral ischemia, the logistic regression model for predicting mortality had an AUC of 0.911.The ACAG is an efficient prognostic marker for aSAH patients. The prognostic model incorporating ACAG could help clinicians evaluate the risk of poor outcomes among aSAH patients and consequently make personalized therapeutics.